Forbruget dykker midlertidigt på grund af corona - Svend Greniman Andersen; Stine Ludvig Bech; Simon Juul Hviid; Andreas Kuchler (Danmarks Nationalbank, 2020)
– The corona epidemic has reduced the consumption of Danish households, which will temporarily lower the consumption rate. For a prolonged period, Danish households have saved and are in general well equipped for a contraction of the Danish economy. Therefore, the consumption rate is expected to relatively quickly return to its pre-corona epidemic level. However, a longer lasting epidemic and contraction of the Danish economy can further reduce household consumption.
Keywords: 330; Privater Konsum; Coronavirus; Dänemark